2020
DOI: 10.1515/mlt-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

“Danger of a single story”: Pre-service teachers’ of color use of an online discussion board to discuss the essentialization of culture

Abstract: The current demographic gap that exists between a predominantly white and female teacher force and an increasing diverse K-12 student population has prompted a focus on the recruitment and retainment of teachers of color. These recruitment and retainment efforts at times come at “the expense of preparation” (Gist, 2014, p. 266). Further, education scholars have critiqued teacher education due to the exclusion of the voices and experiences of pre-service teachers of color (Sleeter & Thao, 2007; Takimoto Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thus far, the review of the literature has shown how research on DEI practices at independent schools could benefit from an examination of kindergarten teachers' and their (Gay, 1999;Sleeter, 1996) and the processes in which and how their identities have been expressed have always been done so with an acute awareness of how others have perceived them (Braunstein et al, 2021). Then, this subsection proceeds with a review of the literature illuminating what specific factors Teachers of Color have considered when constructing their in-school identities (Burant et al, 2002;V.…”
Section: Negotiating Multiple Identitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, the review of the literature has shown how research on DEI practices at independent schools could benefit from an examination of kindergarten teachers' and their (Gay, 1999;Sleeter, 1996) and the processes in which and how their identities have been expressed have always been done so with an acute awareness of how others have perceived them (Braunstein et al, 2021). Then, this subsection proceeds with a review of the literature illuminating what specific factors Teachers of Color have considered when constructing their in-school identities (Burant et al, 2002;V.…”
Section: Negotiating Multiple Identitiesmentioning
confidence: 99%
“…In their study, as an instructor of a diversity in education course for a teacher education program, Braunstein showed Ngozi Adichie's (2009) TED Talk Danger of a Single Story. Braunstein then asked her preservice students to share, via an online discussion board, what they wished others knew about their identity; these responses were later analyzed by Braunstein et al (2021). One of the themes that emerged from their findings was how preservice Teachers of Color felt their identities were often reduced to essentializing and racializing discourses in which their racial identities were misidentified or conflated with broader racial identity labels, or they were presumed to have been accepted into the program to fill an ethnic quota.…”
Section: Negotiating Multiple Identitiesmentioning
confidence: 99%
See 1 more Smart Citation